Visualisasi Manajemen Keuangan - Indahwati Indahwati; Ni Ketut Yulia Agustini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Financial management is one of the main courses at the Faculty of Economics and Business. However, this course is often considered a difficult subject for some students. This study is a qualitative study with a theoretical perspective by constructing a financial management visualization scheme. The aim is to provide illustrations that provide a complete view to make it easier to understand financial management. The discussion is given in a comprehensive manner regarding the function of financial management, namely seeking funds in an efficient composition, making investments effectively, and dividing profits (dividends) strategically as shown in a brief financial report. This financial management function is carried out to achieve company goals, namely the value of the firm in the form of stock prices. The results show that it does not only provide benefits for shareholders or owners, but also long-term benefits for stakeholders or related parties in the form of corporate social responsibility.